MODERN ECONOMIC THOUGHT: DUALITY AND DIRECTION* - Uraz Baimuratov, (Academic Journal of Physical and Chemical Sciences, 2019)
The article describes the evolution of economic thought from monism to dualism. Like the world economy of individual countries, economic thought is also dual. The peculiarities of the economic teachings of harmonious and disharmonious economy are given. Including a comparative analysis of the features of Harmony and disharmony in all spheres of society, including economic one. The concept of features and objective laws of harmonious economy was formulated. Ways of using the new methodological vector for the stable development of national economies were proposed.